Nekdanja slovita operna in koncertna pevka Amalie Schneeweiss-Joachim (1839-1899) je bila rojena v Mariboru - Špendal, Manica (Muzikološki zbornik, 2010)
The opera and concert singer, mezzo-soprano, alto, and contralto, Amalie Schneeweiss (pseudonim Weiss) - Joachim (b. on May 10, 1839) is to be regardedas one of the most important personalities born in Maribor.
Keywords: 19.st.; 19th century; Amalie, Schneeweiss-Joachim, 1839-1899; concert singers; koncertne pevke; Maribor; opera singers; operne pevke